Single Mach-Zehnder interferometer based optical Boolean logic gates - Reis, Cláudia (2012)
In this paper, we demonstrate different optical logic gates using a single Mach-Zehnder interferometer with controlled phase modulators in each arm. The operational conditions to obtain 16 optical logic circuits, using the same design, are investigated and are a result of a constructive or destructive interference process. The proposed configuration presents significant low complexity and high scalability, and its feasibility is evaluated through numerical simulations.